Challenges of Elderly Coffee Farmers: Exploring Fall Risks and Associated Hypertension in Alas Lanjang, Bondowoso - Salsabila, Nadia Putri; Susumaningrum, Latifa Aini; Rasni, Hanny; Kurdi, Fahruddin; Ati, Niken Asih Laras (Al-Hijrah Indonesia, 2025)
Elderly farmers faced high health risks, particularly from Non-Communicable Diseases (NCDs), with hypertension being a significant issue. The elderly were vulnerable to hypertension due to physiological changes affecting their well-being. Hypertension in the elderly increases the risk of falls, which could cause physical injuries and psychological impacts. This study aimed to analyze the characteristics of elderly farmers and describe the fall risk among hypertensive elderly farmers in Blimbing Village, Klabang Subdistrict, Bondowoso Regency. This research used a descriptive quantitative design with a cross-sectional approach. The study population included 90 elderly farmers in Dusun Alas Lanjang, with a sample of 60 hypertensive elderly farmers meeting the inclusion criteria. Data were collected using the Morse Fall Scale questionnaire to assess fall risk and demographic characteristics. The study results indicate that most respondents were 60-74 years old (68.3%), with the majority being female (56.7%). Most respondents had no formal education (61.7%). The most prevalent type of hypertension among respondents was Stage 1 hypertension, with 30 (50%) respondents, and Stage 2 hypertension, with another 30 (50%) respondents. Results from the Morse Fall Scale showed 58 (96.7%) respondents at high risk of falls and 2 (3.3%) respondents at low risk. These findings indicated a high risk of falls among hypertensive elderly farmers in Blimbing Village, necessitating appropriate interventions to prevent falls and related health complications.